2021
DOI: 10.3390/w13070940
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Event Isotopic Changes in Water Vapor and Precipitation in South China

Abstract: Synchronous observations of the isotopic composition of water vapor and precipitation for 24 rain events were performed. Rain events driven by low-level jets exhibited similar isotopic changes in precipitation and water vapor. The vertical activity of water vapor in convection causes the isotopic variation in precipitation to be opposite to that of water vapor. Isotopic changes of precipitation in low-pressure systems were partially synchronized with that of water vapor at high but not low water vapor concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Furthermore, in this study Δ d ‐excess TF–RF and Δ d ‐excess SF–RF increased progressively towards the end of the events, whereas Δ d ‐excess SF–TF decreased slightly. As mentioned above, this is because the sub‐cloud evaporation effect and a typical decrease in precipitation amount and raindrop size at the end of the rainfall event lead to the depletion of heavy isotopes in precipitation and lower d‐excess (e.g., Li et al, 2021). However, the canopy selection effect may explain the higher Δ d ‐excess TF–RF and Δ d ‐excess SF–RF at the end of the events.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in this study Δ d ‐excess TF–RF and Δ d ‐excess SF–RF increased progressively towards the end of the events, whereas Δ d ‐excess SF–TF decreased slightly. As mentioned above, this is because the sub‐cloud evaporation effect and a typical decrease in precipitation amount and raindrop size at the end of the rainfall event lead to the depletion of heavy isotopes in precipitation and lower d‐excess (e.g., Li et al, 2021). However, the canopy selection effect may explain the higher Δ d ‐excess TF–RF and Δ d ‐excess SF–RF at the end of the events.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in many cases such as stratiform rain systems, the S75 model outputs may not differ significantly from closed model outputs due to small differences between the isotope composition of the droplet and the atmosphere. On the other hand, smaller droplet sizes from stratiform rain may increase the importance of these effects (Li et al, 2021; Bolin, 1958). In other cases, such as convective thunderstorm systems where droplets form under cold conditions high in the troposphere, closed system models may function better in predicting isotope evolution of droplets because the droplet‐atmosphere isotope composition differences can be quite high (Bony et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also use S75 to better understand precipitation processes at a local level. Using this model in a study in South China, Li et al (2021) suggest that isotope exchange has a stronger signature on precipitation when raindrop radii are smaller, and that isotope exchange with surrounding vapour limits the enrichment of the rain droplets during evaporation. Recently, Vimeux and Risi (2021) evaluated precipitation in the Andes Mountains in Bolivia and found that S75 was not sufficient to explain the isotope observations of rainfall in this region.…”
Section: Introductionmentioning
confidence: 99%
“…Precipitation samples plotting below the GMWL are indications of re-evaporation of raindrops during precipitation events (Banda, Rivett, Zavison, Kamtukule, & Kalin, 2021). Small size raindrops of stratiform precipitation are inclined to kinetic fractionation under the cloud base, favoring exchange with surrounding air and re-evaporation (Li, Tang, & Cui, 2021). The notable deviation from the GWML of the Kunming precipitations, with a regression line equation of δ 2 H=6.56 δ 18 O-2.9 would be from significant evaporative enrichment occurred during rainfall falling process (2021).…”
Section: Comparison Of Antananarivo Data With Regional and Internatio...mentioning
confidence: 99%